Investigation of Computer Audiocontroller Converters - Gražulevičius, A.; Gražulevičius, G. (Elektronika ir Elektrotechnika, 2000)
The methods for the investigation of audiocontrollers converters without measuring devices and special stands are proposed. The computer and plugged in investigative audiocontroller offer to use for these purpose. The investigation methods well-founded of the MATLAB package are used for the modeling ideal analog to digital converter (ADC) work and calculating the effective number of bits (ENOB) of real ADC, and evaluating audiocontroller noise characteristics. The signal recording level and digital to analog converter (DAC) influence for ADC ENOB is also investigated in this article.Possible errors of ADC ENOB calculations are analysed. Adjusting of the methods examples are presented.